Analisis Kontribusi Pajak Daerah dan Retribusi Daerah terhadap Pendapatan Asli Daerah (PAD) di Sumatera Utara - Syaifullah (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to analyze the contribution of local taxes and levies to Local Own-Source Revenue (PAD) in North Sumatra Province during the 2018-2022 period. The population in this study comprises all 33 districts/cities in North Sumatra Province, with a sample of 30 districts/cities selected using purposive sampling technique. This research employs a quantitative approach with descriptive and inferential analysis. The data analysis methods include contribution analysis, trend analysis, effectiveness analysis, and panel data regression analysis. The results show that: (1) The average contribution of local taxes to PAD is 25.58% with